1994
DOI: 10.1161/01.cir.89.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlations in hypertrophic cardiomyopathy. Insights provided by comparisons of kindreds with distinct and identical beta-myosin heavy chain gene mutations.

Abstract: BACKGROUND We have previously described two distinct mutations in the beta-myosin heavy chain gene with markedly different clinical presentations and outcome: The 908Leu-->Val mutation was associated with a low disease penetrance and a benign prognosis. In contrast, the 403Arg-->Gln mutation in a Caucasian kindred was associated with a 100% disease penetrance and high incidence of sudden cardiac death. Recently, another mutation, 606Val-->Met, has been reported to be associated with "near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(91 citation statements)
references
References 57 publications
2
88
0
1
Order By: Relevance
“…In spite of exceptions to previously published genotype-phenotype correlations, [12][13][14]18,19 hopes that genetic testing will become a routine clinical test with prognostic value remain. 9,23-26 An HCM gene chip containing known mutations has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of exceptions to previously published genotype-phenotype correlations, [12][13][14]18,19 hopes that genetic testing will become a routine clinical test with prognostic value remain. 9,23-26 An HCM gene chip containing known mutations has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11 In contrast, 6 particular missense mutations in MYH7 (N232S, G256E, F513C, V606M, R719Q, and L908V), as well as the S179F mutation in troponin T (TNNT2) and the D175N mutation in ␣-tropomyosin (TPM1), have been designated as benign mutations with no increased risk of SCD. 8 -10,12-17 Several studies have reported exceptions to these genotypephenotype correlations [12][13][14]18,19 ; however, the veracity with which the genetic substrate predicts the clinical outcome and the frequency of specific mutations are unknown. From a cohort of nearly 300 unrelated individuals with HCM seen at a single tertiary referral center, we sought to determine the frequency of 8 published benign mutations and to examine the clinical course of the individuals harboring these mutations.…”
mentioning
confidence: 99%
“…To date more than 70 different mutations have been identified in the MYH7 gene (Table 1). Some are associated with sudden death (p.R403Q), but several also have a benign phenotype (p.V606M) (Epstein et al 1992;Fananapazir and Epstein 1994).…”
Section: Genetic Basis Of Fhcmentioning
confidence: 99%
“…Clinical characteristics of HCM vary from a benign asymptomatic course to severe heart failure and sudden death. Molecular genetic studies [1][2][3][4][5][6][7] have shown that HCM may be caused by mutations in several sarcomeric genes, including TPM1, that may determine clinical outcome. Most ␤-myosin heavy chain gene (MYH7) mutations, such as R403Q, are associated with high disease penetrance and a poor prognosis.…”
mentioning
confidence: 99%
“…4 In contrast, the few MYH7 mutations that have a benign prognosis, such as L908V and G256E, are associated with a low disease penetrance. 5 HCM caused by myosin-binding protein-C gene (MYBPC3) is characterized by low disease penetrance (Ϸ60%), mild cardiac phenotype in young subjects, and a favorable prognosis. [1][2][3] HCM due to cardiac troponin-T gene (TNNT2) is usually associated with relatively low disease penetrance (Ϸ80%) and mild LVH but a high incidence of sudden death.…”
mentioning
confidence: 99%